Penerapan Model Teams Games Tournament (TGT) dan Media Peta dalam Pembelajaran IPS di Sekolah Dasar - Nia Citra Nadila; Aprina Ayu Wulandari; Vinny Rachmadini (CV. Lentera Literasi Indonesia, 2026)
This study aims to describe the results of a field study on the implementation of the Teams Games Tournament (TGT) learning model and the use of map media in Social Studies learning on the topic of the surrounding environment at SD Muhammadiyah 14 Balayudha Palembang. The research employed a qualitative descriptive approach through classroom observation, interviews with teachers and students, and group reflections. The findings revealed that the teacher applied lecture and discussion methods using the TGT approach, while the learning media were still limited to the whiteboard. Students showed enthusiasm, motivation, and active participation, although the lack of technological facilities became a major constraint in supporting visualization. Literature analysis suggests that combining the TGT model with map media can enhance spatial understanding, student engagement, and overall learning outcomes in Social Studies. This study contributes to providing insights for teachers to develop more interactive and contextual learning strategies by integrating cooperative models and visual learning media in elementary Social Studies classes.